Investigation of Shock Initiation in Covered Charges under Shock Wave and Fragment Impacts - Xingwang Chen; Jinxiang Wang; Kui Tang; Hongfei Wang; Yuanbo Li (Shock and Vibration)
In the current work, a series of step-by-step research methods have been applied to address the damaging effects of near-field strong shock waves and high-speed fragments on covered charge. In the first step, the defects of covered plates due to high-speed fragments were simplified to penetrated notches, and then, these notches were used to evaluate the impact of shock wave loads on charges covered with metal plates. In the next step, we developed a theoretical model to take into account the shock initiation of charges covered with defected metal plates. Explosive initiation standards coupled with shock wave evolution characteristics were applied to specify the crucial conditions of explosive detonation. Finite element program, for instance, was applied for the simulation of shock initiation processes in pressed charges (when TNT was covered with a steel plate containing a penetrated notch), and then, numerical simulations were validated by experimental findings. Finally, the results obtained from the numerical simulations and theoretical model were applied to evaluate the impacts of shock wave intensity, the thickness of covered metal plate, and the geometrical features of penetrated notch on pressed charge shock initiation. The least squares method was applied to determine critical initiation criteria (n and K). Theoretical calculation results were found to be highly consistent with those obtained from numerical simulations, indicating that covered metal plates significantly contributed to charge protection. The results also revealed that notches could undermine the protective function of covered plates and the size and shape of notch significantly affected charge critical detonation distance. Critical detonation distances of noncontact explosions were found to be 25 and 81 mm for a 3 mm thick pressed TNT in the presence and absence of 45# steel-covered plate, respectively. According to the results, increase in the diameter of covered plates containing a cylindrical notch increased pressed TNT critical detonation distance. When dealing with a covered plate containing a normally reflected frustum notch, however, we figured out that any increase in normal reflection slope could decrease pressed TNT critical detonation distance.